Physical Characteristic and In-Vitro Bioactivity Property of Sintered Glasses made via Sol-Gel and Powder Sintering Process - Syed Nuzul Fadzli, Syed Adam (Penerbit UniMAP (UniMAP Press), 2022)
Link to publisher's homepage at https://aset.unimap.edu.my